2010
DOI: 10.5539/ijms.v2n2p57
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Service Quality on Customer Loyalty: A Study of Banks in Penang, Malaysia

Abstract: The emergence of new forms of banking channels such as Internet banking, Automated Teller Machines (ATM), phone banking and also maturing financial market and global competition have forced bankers to explore the importance of customer loyalty. Therefore, studies need to focus on the changing role of the banking system and its dynamic financial market. The underlying model of SERVQUAL (Parasuraman et al., 1988) with five dimensions was used by this research to evaluate the impact of service quality on customer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
157
6
27

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(218 citation statements)
references
References 36 publications
28
157
6
27
Order By: Relevance
“…With regards to evaluation of particular ATM usage experience, studies have found that customers are satisfied with ATM banking in Malawi (Mwatsika, 2014), Pakistan (Khan, 2010), India (Komal, 2009) and Malaysia (Kheng, et al, (2010). However, not many studies have looked into whether satisfaction with ATM banking performance translates into satisfaction with the bank.…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…With regards to evaluation of particular ATM usage experience, studies have found that customers are satisfied with ATM banking in Malawi (Mwatsika, 2014), Pakistan (Khan, 2010), India (Komal, 2009) and Malaysia (Kheng, et al, (2010). However, not many studies have looked into whether satisfaction with ATM banking performance translates into satisfaction with the bank.…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…Hasil Penelitian ini tidak mendukung penelitian Nurul Qomariah (2012) yang menyatakan kepuasan mahasiswa tidak berpengaruh terhadap loyalitas nasabah, karena nilai signifikasi sebesar 0,9 namun selaras dengan hasil penelitian yang dilakukan oleh Kheng, Mahamad, Ramayah, and Mosahab (2010) dengan nilai koefisien 0,00. Jika dikaitkan dengan loyalitas nasabah, maka kualitas pelayanan berperan sebagai variabel pendahulu bagi terciptanya kepuasan nasabah (Dick dan Basu, 1994 …”
Section: Pengaruh Kepuasan Mahasiswa Secara Tidak Langsung Terhadap Lunclassified
“…In the context of banking services, Bloemer et al (1995) revealed that the reliability and efficiency of service impacts on the level of customers' loyalty. Thus, Kheng et al (2010) found a direct positive connection between quality factors, for example, reliability, empathy and assurance and customer loyalty. Zahork and Rust (1992) argued that modeling perceived quality as an influencing component of customer loyalty as a dependent develop.…”
Section: Relationship Between E-service Quality and E-loyaltymentioning
confidence: 99%